2012
DOI: 10.5152/akd.2012.069
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of maximum P-wave duration and dispersion after percutaneous closure of atrial septal defects: Comparison of two septal occluders

Abstract: Analysis of maximum P-wave duration and dispersion after percutaneous closure of atrial septal defects: Comparison of two septal occludersAtriyal septal defektlerin perkütan kapatılması sonrası maksimum P dalga süresi ve dispersiyon analizi: İki septal oklüderin karşılaştırılması Original Investigation Özgün Araşt›rma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
0
7
1
Order By: Relevance
“…the "foreign body" effect of the device had caused inflammation of the atrial myocardium. 39 In contrary to our study, Başpınar et al found a decrease in mean P wave dispersion of 27 atrial septal defect patients whose defects were closed by surgery. 6 In Guray's study, 34 adult patients whose defect closed by surgery were analysed.…”
contrasting
confidence: 99%
“…the "foreign body" effect of the device had caused inflammation of the atrial myocardium. 39 In contrary to our study, Başpınar et al found a decrease in mean P wave dispersion of 27 atrial septal defect patients whose defects were closed by surgery. 6 In Guray's study, 34 adult patients whose defect closed by surgery were analysed.…”
contrasting
confidence: 99%
“…The return to the baseline of the bottom of the trace was considered to be the end of the P-wave. The difference between the maximum and minimum P-wave duration calculated from any derivation of the 12-lead ECG was defined as the PD (PD = Pmaximum - Pminimum) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, immediately after ASD closure an increase in both maximum P-wave duration and PWD was noted, irrespective of the device used (Amplatzer vs. Figulla septal occluder) [22]. Our results underline the dynamics of myocardial remodelling after ASD closure.…”
Section: Discussionmentioning
confidence: 47%